The Influence of Strategic Thinking to the Organization Performance of Arabic Gulf Oil Company-Libya - Alhmmali, Mansour Alshrif (2008)
The aims of this study are to investigate whether there is any relationship between strategic thinking and organization performance. The quantitative data were processed using a SPSS version 14.0 program. Descriptive statistics such as frequency and percentage used to measure the percentage of returned questionnaire and also be used to describe the respondents’ profile such as their gender, educational background, their length of service, job level, age, and department. Correlation and multiple regressions used for inferential statistics. The Pearson correlation used to measure the significance of linear bivariate between the independent and dependent variables thereby achieving the objective of this study. This thesis concludes that strategic thinking can never be taken for granted in organization performance, but must always be examined at the interaction level of its constitution and reproduction, within the regimes of representation and classification in which practitioners operate. Such regimes of representation and classification are immanent in a variety of managerial tools and organizational systems and must therefore be examined in greater details.